The functioning of the music industry in contemporary Ukraine: from concert to copyright - Пархоменко, Ірина (Київський національний університет імені Тараса Шевченка, 2023)
The relevance of the research lies in the need to determine the fundamental principles of the functioning of the music industry in contemporary Ukraine, as reflected in its policies and legislation, as Ukrainian artists continue to actively create music products despite the ongoing armed conflict. Artists in Ukraine require transparent mechanisms for generating their own income, based on a coordinated system of legislation. The article explores the fundamental principles of the functioning of the music industry in contemporary Ukraine, as reflected in Ukraine's cultural policy and legislation, through an analysis of cultural policies regarding music and concert activities of artists in various periods of the Soviet Union, and by comparing it with the current reality in the Ukrainian music market. The study used a systemic and dialectical approach, as well as methods of analysis, synthesis, description, and comparison. The terminological basis of Ukrainian cultural legislation pertaining to the functioning of the music industry and market is analyzed. The absence of terms designating activities related to the production of commercial music products is identified, despite the fact that the music market continues to operate even in times of martial law. An analysis of the fundamental principles of the USSR's cultural policy regarding music in different periods is conducted, and the main state authorities responsible for controlling the concert activities of artists are identified. In the conclusions, it is emphasized that the roots of the fundamental principles of today's cultural policy in the field of music and concert activities in Ukraine still lie in the narrative of concert activities, as it was in the Soviet Union, but without ideological component. Although there are established norms of copyright legislation that allow for progress towards protecting the rights of Ukrainian artists. Further research can focus on studying the path to the popularity of a musical performer in the Soviet Union and comparing it with the situation in Ukraine: from independence to the present day.

Здійснено дослідження засадничих принципів функціонування музичної індустрії в сучасній Україні, які відображені в культурній політиці та законодавстві України, шляхом проведення аналізу політики в сфері культури щодо музики та концертно-гастрольної діяльності артистів в різні періоди існування Радянського Союзу і співвідношення з сучасним станом справ на музичному ринку України. Використано системний та діалектичний підхід, методи аналізу і синтезу, опису і порівняння. Проаналізовано термінологічну базу українського законодавства про культуру, яка стосується функціонування музичної індустрії та ринку. Визначено відсутність термінів на позначення діяльності щодо виробництва комерційного музичного продукту, хоча музичний ринок продовжує працювати навіть в умовах воєнного стану. Здійснено аналіз засадничих принципів культурної політики СРСР щодо музики в різні періоди та визначено основні органи державної влади, які здійснювали контроль над концертно-гастрольною діяльністю артистів.
Функціонування музичної індустрії в сучасній Україні: від концерту до одиниці авторського права
Keywords: музична індустрія; музичний твір; авторське право; концерт; роялті; музичний продукт; артист; музика; культурна політика; music industry; musical composition; copyright; concert; royalty; music product; artist; music; cultural policy